Maximum topological distances based indices as molecular descriptors for QSPR 4 : Modeling the enthalpy of formation of hydrocarbons from elements - Mercader, Andrew Gustavo (2001)
The enthalpy of formation of a set of 60 hydroarbons is calculated on the basis of topological descriptors defined from the distance and detour matrices within the realm of the QSAR/QSPR theory. Linear and non-linear polynomials fittings are made and results show the need to resort to higher-order regression equations in order to get better concordances between theoretical results and experimental available data. Besides, topological indices computed from maximum order distances seems to yield rather satisfactory predictions of heats of formation for hydrocarbons.